PENGARUH PROGRAM TAHFIZ AL-QUR’AN TERHADAP KARAKTER RELIGIUS SISWA DI SD IT ALAM TAHFIZ ADZIKRA: STUDI MIXED METHOD DENGAN ANALISIS STATISTIK SPSS - Herlina Yusroh Nst; Martin Kustati; Nana Sepriyanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of the Tahfiz Al-Qur’an program on the development of students’ religious character at SD IT Alam Tahfiz Adzikra. Using a Mixed Methods design with an Explanatory Sequential approach, this research combines quantitative data collected through a character assessment scale analyzed using SPSS version 26 and qualitative data obtained from in-depth interviews with Tahfiz teachers and field observations. The research subjects consisted of the entire population of 78 students from grades 1 to 6. Descriptive statistical analysis showed an increase in the mean score of religious character from 65.42 (Fair category) before the program to 82.15 (Good category) after the program. The hypothesis testing using the Paired Sample T-Test yielded a significance value of 0.000 (< 0.05), indicating a statistically significant effect. Qualitative findings revealed that the combination of tikrar (repetition), talaqqi (direct recitation to the teacher), and simai (listening and evaluation) methods, implemented four times a week, was effective in fostering worship independence, good manners, and honesty. The main supporting factors were the competence of certified teachers and a parental monitoring system, while the primary obstacle was the consistency of muroja’ah (Qur’anic revision) at home. This study concludes that the integration of Qur’anic memorization with daily character habituation is an effective strategy for developing holistic religious character.